2012
DOI: 10.1182/blood-2011-09-379263
|View full text |Cite
|
Sign up to set email alerts
|

Signaling and cytoskeletal requirements in erythroblast enucleation

Abstract: To understand the role of cytoskeleton and membrane signaling molecules in erythroblast enucleation, we developed a novel analysis protocol of multiparameter high-speed cell imaging in flow. This protocol enabled us to observe F-actin and phosphorylated myosin regulatory light chain (pMRLC) assembled into a contractile actomyosin ring (CAR) between nascent reticulocyte and nucleus, in a population of enucleating erythroblasts. CAR formation and subsequent enucleation were not affected in murine erythroblasts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
136
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(144 citation statements)
references
References 44 publications
3
136
1
1
Order By: Relevance
“…Although an abnormal level of circulating nucleated definitive cells are observed in embryos deficient for the DNASE2A, MAF or palladin macrophage proteins (Kawane et al, 2001;Kusakabe et al, 2011;Liu et al, 2007), ablating the majority of macrophage cells does not automatically yield an abundance of nucleated red cells in circulation (Chow et al, 2013;Ramos et al, 2013). In addition, there are a number of structural, enzymatic and chromatin-associated erythroid cell factors that play an intrinsic role in morphologically preparing the cell for proper nuclear extrusion (Ji et al, 2011;Keerthivasan et al, 2011;Konstantinidis et al, 2012;Ney, 2011;Ubukawa et al, 2012;von Lindern, 2006). In the case of EKLF, the abundance of nucleated red cells in circulation seen in its absence or in the CDA KLF1/E325K patients may not only result from defective function in the island macrophage, but also as part of the global erythroid-specific panoply of EKLF targets that include ones important for these final maturation steps.…”
Section: Membrane Protein Dynamics and Complexitymentioning
confidence: 99%
“…Although an abnormal level of circulating nucleated definitive cells are observed in embryos deficient for the DNASE2A, MAF or palladin macrophage proteins (Kawane et al, 2001;Kusakabe et al, 2011;Liu et al, 2007), ablating the majority of macrophage cells does not automatically yield an abundance of nucleated red cells in circulation (Chow et al, 2013;Ramos et al, 2013). In addition, there are a number of structural, enzymatic and chromatin-associated erythroid cell factors that play an intrinsic role in morphologically preparing the cell for proper nuclear extrusion (Ji et al, 2011;Keerthivasan et al, 2011;Konstantinidis et al, 2012;Ney, 2011;Ubukawa et al, 2012;von Lindern, 2006). In the case of EKLF, the abundance of nucleated red cells in circulation seen in its absence or in the CDA KLF1/E325K patients may not only result from defective function in the island macrophage, but also as part of the global erythroid-specific panoply of EKLF targets that include ones important for these final maturation steps.…”
Section: Membrane Protein Dynamics and Complexitymentioning
confidence: 99%
“…Konstantinidis et al suggested that the fusion of lipid rafts upon docking of autophagosomes with the cytoplasmic membrane is an important process during the terminal phase of enucleation. 7 This cartoon is based on Figure 6C in the study of Keerthivasan et al support of a direct role of this latter complex in enucleation, the authors found that knockdown of the genes reduces the efficiency of enucleation of primary human erythroblasts. Based on their own findings, they confirm that overexpression of survivin in cells dramatically increases the ratio of enucleated cells.…”
Section: Involvement Of a Novel Survivin-based Protein Complex In Enumentioning
confidence: 99%
“…[1][2][3][4][5][6] It has been recently reported that, in the very last stage of enucleation, not only proteins but also specialized regions of the lipid bilayer, known as lipid rafts, as well as organelles participate in the extrusion of the nucleus. 7 Approximately 120 million reticulocytes are generated each minute in our body. Macrophages phagocyte and recycle a similar number of extruded nuclei and other organelles, such as mitochondria.…”
mentioning
confidence: 99%
“…NMHC IIA, but not IIB or IIC could be detected in megakaryocytes and platelets (Marigo et al, 2004;Maupin et al, 1994) where NMHC IIA is crucial for organelle distribution (Pertuy et al, 2014). Enucleation of erythroid cells is promoted by actinomyosin ring contraction between the incipient reticulocyte and the nucleus that is induced by Rac-GTPase-dependent myosin regulatory light chain phosphorylation (Ji et al, 2008;Konstantinidis et al, 2012;Koury et al, 1989). Because we noticed increased enucleation of hnRNP-K-depleted K562 cells (Fig.…”
Section: Differential Hnrnp-k−rna Binding In Erythroid Maturationmentioning
confidence: 99%